Biochemical characterization of a low molecular weight aspartic protease inhibitor from thermo-tolerant bacillus licheniformis: kinetic interactions with pepsin - Kumar, Ajit; Rao, Mala (Biochimica et Biophysica Acta-General Subjects, 2006)
The present article reports a low molecular weight aspartic protease inhibitor, API, from a newly isolated thermo-tolerant Bacillus licheniformis. The inhibitor was purified to homogeneity as shown by rp-HPLC and SDS-PAGE. API is found to be stable over a broad pH range of 2-11 and at temperature 90 degrees C for 2 1/2 h. It has a Mr (relative molecular mass) of 1363 Da as shown by MALDI-TOF spectra and 1358 Da as analyzed by SDS-PAGE The amino acid analysis of the peptide shows the presence of 12 amino acid residues having Mr of 1425Da. The secondary structure of API as analyzed by the CD spectra showed 7% alpha-helix, 49% beta-sheet and 44% aperiodic structure. The Kinetic studies of Pepsin-API interactions reveal that API is a slow-tight binding competitive inhibitor with the IC(50) and K(i) values 4.0nM and (3.83 nM - 5.31 nM) respectively. The overall inhibition constant K(i)* value is 0.107 +/- 0.015 nM. The progress curves are time-dependent and consistent with slow-tight binding inhibition: E+I reversible arrow (k(4), k(5)) EI reversible arrow (k(6), k(7)) EI*. Rate constant k(6) = 2.73 +/- 0.32 s(-1) reveals a fast isomerization of enzyme-inhibitor complex and very slow dissociation as proved by k(7)=0.068 +/- 0.009s(-1). The Rate constants from the intrinsic tryptophanyl fluorescence data is in agreement with those obtained from the kinetic analysis; therefore, the induced conformational changes were correlated to the isomerization of EI to EI*. (c) 2006 Elsevier B.V. Ail rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; enzyme kinetic; Pepsin; Slow-tight binding inhibition